LPIC-2 : Linux professional instutute certification : study guide exam 201 and exam 202 / Christine Bresnahan; Roderick W Smith - Bresnahan, Christine
Full coverage of the latest LPI-level 2 exams, with bonus online test bank LPIC-2 is the one-stop preparation resource for the Linux Professional Institute's Advanced Level certification exam.